2015
DOI: 10.1155/2015/167406
|View full text |Cite
|
Sign up to set email alerts
|

High Definition Colonoscopy Combined with i-SCAN Imaging Technology Is Superior in the Detection of Adenomas and Advanced Lesions Compared to High Definition Colonoscopy Alone

Abstract: Background. Improved detection of adenomatous polyps using i-SCAN has mixed results in small studies. Utility of i-SCAN as a primary surveillance modality for colorectal cancer screening during colonoscopy is uncertain. Aim. Comparing high definition white light endoscopy (HDWLE) to i-SCAN in their ability to detect adenomas during colonoscopy. Methods. Prospective cohort study of 1936 average risk patients who had a screening colonoscopy at an ambulatory procedure center. Patients underwent colonoscopy with h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…One tandem study reported a significantly lower adenoma miss rate with i‐scan in comparison with HD WL colonoscopy, but another concluded that there were no significant differences . Moreover, one recent non‐randomized controlled study demonstrated that i‐scan had a significantly higher detection rate for adenoma and advanced adenoma in comparison to HD WL endoscopy …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One tandem study reported a significantly lower adenoma miss rate with i‐scan in comparison with HD WL colonoscopy, but another concluded that there were no significant differences . Moreover, one recent non‐randomized controlled study demonstrated that i‐scan had a significantly higher detection rate for adenoma and advanced adenoma in comparison to HD WL endoscopy …”
Section: Resultsmentioning
confidence: 99%
“…44 Moreover, one recent non-randomized controlled study demonstrated that i-scan had a significantly higher detection rate for adenoma and advanced adenoma in comparison to HD WL endoscopy. 45 Two meta-analyses in 2011 and 2013 confirmed the superiority of capsule endoscopy (CE) with targeted biopsy over SD WL colonoscopy with random biopsy (6% increase in the yield for dysplasia). 46,47 As a result, many international guidelines now recommend the routine use of pancolonic chromoendoscopy with targeted biopsy for neoplasia surveillance in patients with IBD.…”
Section: Statement 3-1: Image-enhanced Endoscopy (Iee) Can Improve Pomentioning
confidence: 99%
“…This enhances the contrast of the light and dark, therefore improving the visualization and providing a more detailed examination of the mucosal surface structure. Bowman et al () stated that surface enhancement improves the ability to distinguish between the borders of the abnormal and normal mucosa. This mode improves the efficiency of polyp detection.…”
Section: Commercial Colonoscopy Devices Performance and Market Analysismentioning
confidence: 99%
“…The second mode is contrast enhancement. This creates a blue‐tint image as it suppresses the wavelength of red and green, allowing for the enhanced visualization of the depth of the mucosal surface (Bowman et al, ). Contrast enhancement can also be utilized to visualize irregularities, which may be unnoticed if white light colonoscopy is solely utilized (Cho, ).…”
Section: Commercial Colonoscopy Devices Performance and Market Analysismentioning
confidence: 99%
See 1 more Smart Citation